Investigating the Impact of the of Technological Developments, Environmental Quality, and Economy on Tourism Receipts in Indonesia - Sulistiyowati, Maya; Rahmayani, Dwi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This paper uses a panel technique to investigate the relationship between Technological Developments, Environmental, and GDP Quality on Tourism Receipts in Indonesia (including 33 provinces) for the 2011-2022 period. As a country with rich natural, cultural and ancestral heritage, Indonesia has the potential to attract foreign tourists. Especially with technological advancements that have made tourism promotion possible on a massive scale. On the other hand, an increase in the number of tourists has an impact on the environment as explained in the theory of the Environmental Kuznet Curve (EKC). The research method used is Vector Error Correction Model (VECM) model and Granger causality test. Environmental quality is measured through the Environmental Quality Index indicator. Meanwhile, technology development is measured through the Information and Communication Technology Development Index. The research results explain that Economy, Environmental Quality, and Technological Developments have a positive impact on Tourism Receipts in Indonesia. Therefore, it is important for the government to utilize digital technology to introduce Indonesia's tourism wealth. The increase in tourists must also be accompanied by efforts to protect the environment so that it does not have a negative impact on environmental damage.